Smart pack: Online autonomous object-packing system using rgb-d sensor data - Hong, Young Dae; Kim, Young Joo; Lee, Ki Baek (Sensors (Switzerland), 2020)
This paper proposes a novel online object-packing system which can measure the dimensions of every incoming object and calculate its desired position in a given container. Existing object-packing systems have the limitations of requiring the exact information of objects in advance or assuming them as boxes. Thus, this paper is mainly focused on the following two points: (1) Real-time calculation of the dimensions and orientation of an object; (2) Online optimization of the object’s position in a container. The dimensions and orientation of the object are obtained using an RGB-D sensor when the object is picked by a manipulator and moved over a certain position. The optimal position of the object is calculated by recognizing the container’s available space using another RGB-D sensor and minimizing the cost function that is formulated by the available space information and the optimization criteria inspired by the way people place things. The experimental results show that the proposed system successfully places the incoming various shaped objects in their proper positions.
Keywords: Autonomous objects; Desired position; Online optimization; Optimal position; Optimization criteria; Packing systems; Real-time calculations; Rgb-d sensors; 3D bin packing problem; Object-packing; Online optimization; RGB-D sensor